327 Gbps THz silicon photonic interconnect with sub-λ bends - Gupta, Manoj (2023)
Miniaturized photonic devices at the terahertz (THz) band are envisioned to bring significant enhancement to data transfer capacity and integration density for computing and future wireless communications. Broadband silicon waveguiding technology has continuously matured to advance low-loss platforms for integrated solutions. However, challenges are faced in realizing compact waveguiding platforms with different degrees of bends due to bend induced losses and mode distortion. Here, we demonstrate multiple bend incorporated photonic crystal waveguide platforms for multicarrier on-chip transmission. Our silicon interconnect device exhibits optimized bending radius to the free space wavelength ratio of 0.74, without signal distortion and transmission bandwidth of 90 GHz, representing 25.4% fractional bandwidth at 355 GHz. The broadband waveguide interconnect enables an aggregate data transfer rate of 327 Gbps by sending the complex modulated data over multiple carriers. This work augments the development of THz photonic integrated circuit for the future generations of on-chip high data rate interconnect and wireless communication, ranging from the sixth to X generation (6G to XG).